Exciton fine structure inInGaAs∕GaAsquantum dots revisited by pump-probe Faraday rotation - Yugova, I. A.; Greilich, A.; Zhukov, E. A.; Yakovlev, D. R.; Bayer, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Robust manipulation of electron spin coherence in an ensemble of singly charged quantum dots - Greilich, A.; Wiemann, M.; Hernandez, F. G. G.; Yakovlev, D. R.; Yugova, I. A.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Universal behavior of the electrongfactor inGaAs∕AlxGa1−xAsquantum wells - Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Kiselev, A. A.; Bayer, M.; Petrov, V. V.; Dolgikh, Yu. K.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Experimental imaging and atomistic modeling of electron and hole quasiparticle wave functions inInAs∕GaAsquantum dots - Bester, G.; Reuter, Dirk; He, Lixin; Zunger, A.; Kailuweit, P.; Wieck, A. D.; Zeitler, U.; Maan, J. C.; Wibbelhoff, O.; Lorke, A. (Physical Review B)

Measurement of the specific heat of a fractional quantum Hall system - Schulze-Wischeler, F.; Zeitler, U.; v. Zobeltitz, C.; Hohls, F.; Reuter, Dirk; Wieck, A. D.; Frahm, H.; Haug, R. J. (Physical Review B)

Systematic study of carrier correlations in the electron-hole recombination dynamics of quantum dots - Berstermann, T.; Auer, T.; Kurtze, H.; Schwab, M.; Yakovlev, D. R.; Bayer, M.; Wiersig, J.; Gies, C.; Jahnke, F.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Hole levels in InAs self-assembled quantum dots - Blokland, J. H.; Wijnen, F. J. P.; Christianen, P. C. M.; Zeitler, U.; Maan, J. C.; Kailuweit, P.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Ethanol adsorbed on ice: A first-principles study - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Transport properties of magnetic tunnel junctions withCo2MnSielectrodes: The influence of temperature-dependent interface magnetization and electronic band structure - Schmalhorst, J.; Thomas, A.; Kämmerer, S.; Schebaum, O.; Ebke, D.; Sacher, Marc; Reiss, G.; Hütten, A.; Turchanin, A.; Gölzhäuser, A.; Arenholz, E. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Metallodielectric photonic crystal superlattices: Influence of periodic defects on transmission properties - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Gippius, N. A.; Tikhodeev, S. G.; Nau, D.; Giessen, H. (Physical Review B)

Controlling the interaction between localized and delocalized surface plasmon modes: Experiment and numerical calculations - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Kuhl, J.; Giessen, H. (Physical Review B)

Role of quantum capacitance in coupled low-dimensional electron systems - Ruß, M.; Meier, C.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Experimental evidence of the ideal de Haas–van Alphen effect in a two-dimensional system - Wilde, M. A.; Schwarz, M. P.; Heyn, Ch.; Heitmann, D.; Grundler, D.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Tailored quantum dots for entangled photon pair creation - Greilich, A.; Schwab, M.; Berstermann, T.; Auer, T.; Oulton, R.; Yakovlev, D. R.; Bayer, M.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Theory of ultrafast nonlinear optics of Coulomb-coupled semiconductor quantum dots: Rabi oscillations and pump-probe spectra - Danckwerts, J.; Ahn, K. J.; Förstner, Jens; Knorr, A. (Physical Review B)
We investigate the optical properties of a Coulomb-coupled double-quantum dot system excited by coherent light pulses. Basic effects of Coulomb coupling regarding linear and nonlinear optical processes are discussed. By numerically solving the Heisenberg equation of motion we are able to present the temporal evolution of the system’s density matrix for a wide range of coupling parameters. The two main coupling effects in dipole approximation, biexcitonic shift and Förster energy transfer, are investigated and their qualitative and quantitative influence on absorption spectra, Rabi oscillations, and single- and two-pulse excitation is discussed. We present simulated differential transmission spectra to allow for comparison with recent experimental studies.
Keywords: tet_topic_qd

Tight-binding model for semiconductor quantum dots with a wurtzite crystal structure: From one-particle properties to Coulomb correlations and optical spectra - Schulz, S.; Schumacher, Stefan; Czycholl, G. (Physical Review B)

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface - Letzig, T.; Willig, F.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Clean and pyrrole-functionalized Si- and C-terminated SiC surfaces: First-principles calculations of geometry and energetics compared with LEED and XPS - Preuss, M.; Bechstedt, F.; Schmidt, Wolf Gero; Sochos, J.; Schröter, B.; Richter, W. (Physical Review B)

Adsorption of phenylglycine on copper: Density functional calculations - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Structure, energetics, and vibrational spectra of perylene adsorbed on Si(001): First-principles calculations compared with STM and HREELS - Preuss, M.; Miotto, R.; Bechstedt, F.; Rada, T.; Richardson, N. V.; Schmidt, Wolf Gero (Physical Review B)

Strongly bonded water monomers on the ice Ih basal plane: Density-functional calculations - Thierfelder, C.; Hermann, A.; Schwerdtfeger, P.; Schmidt, Wolf Gero (Physical Review B)

Adsorption of water on chlorine-terminated Si(111) from first principles: Substrate-induced ordering versus intermolecular interactions - Biering, S.; Hermann, A.; Schmidt, Wolf Gero (Physical Review B)

Ga-richGaAs(001)surface fromab initiocalculations: Atomic structure of the(4×6)and(6×6)reconstructions - Seino, K.; Schmidt, Wolf Gero; Ohtake, A. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Semiempirical van der Waals correction to the density functional description of solids and molecular structures - Ortmann, F.; Bechstedt, F.; Schmidt, Wolf Gero (Physical Review B)

Temporal decay of coherently optically injected charge and spin currents due to carrier–LO-phonon and carrier-carrier scattering - Duc, H. T.; Vu, Q. T.; Meier, Torsten; Haug, H.; Koch, S. W. (Physical Review B)
The coherent ultrafast optical injection and the temporal evolution of charge and spin currents in semiconductors is analyzed using a microscopic many-body theory. The approach is based on the semiconductor Bloch equations and includes light-field-induced intraband and interband excitations, excitonic effects, and carrier–LO-phonon and carrier-carrier scattering processes. The relaxation effects are treated both in the second Born-Markov approximation and on the level of quantum kinetic theory including memory effects. The dynamics of the charge and spin currents is evaluated numerically for a one-dimensional model system. The dependence of the currents and their decay on the temperature, the excitation intensities, and the frequencies of the incident light fields is discussed. Whereas the overall decay dynamics is described well within the Markov approximation, the quantum kinetic theory predicts additional oscillatory signatures in the current transients.

Thermal stability of magnetic nanostructures in ion-bombardment-modified exchange-bias systems - Höink, V.; Sacher, Marc; Schmalhorst, J.; Reiss, G.; Engel, D.; Weis, T.; Ehresmann, A. (Physical Review B)
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Exciton dephasing via phonon interactions in InAs quantum dots: Dependence on quantum confinement - Borri, P.; Langbein, W.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Optical orientation of electron spins in GaAs quantum wells - Pfalz, S.; Winkler, R.; Nowitzki, T.; Reuter, Dirk; Wieck, A. D.; Hägele, D.; Oestreich, M. (Physical Review B)

Ultrafast electron-phonon interaction of intersubband transitions: Quantum kinetics from adiabatic following to Rabi-oscillations - Butscher, Stefan; Förstner, Jens; Waldmüller, Inès; Knorr, Andreas (Physical Review B)
The interaction of electrons with LO phonons provides an important mechanism of optical dephasing and carrier scattering for the two-dimensional electron gas in semiconductor quantum wells. In this paper, the corresponding ultrafast nonlinearities for off-resonant and resonant intersubband excitations are investigated. Quantum kinetic effects of the electron-phonon interaction and the corresponding violation of the microscopic energy conservation yield a qualitative different picture compared to the standard Markovian theory, if the phonon energy is larger than the intersubband-gap energy.
Keywords: tet_topic_qw

Microscopic theory of electron dynamics and time-resolved two-color two-photon photoemission at semiconductor surfaces - Zeiser, A.; Bücking, N.; Förstner, Jens; Knorr, A. (Physical Review B)
A microscopic description based on the density matrix formalism is developed to describe the dynamics of photoemission of hot electrons at semiconductor surfaces, including the interaction of bulk and surface states. The equations of motion for the electronic occupations and transitions include the interaction with arbitrary optical fields as well as the electron-phonon coupling. Model wave functions are used to qualitatively describe the bulk-surface dynamics and the subsequent time resolved two-photon photoemission s2PPEd spectra. Our results suggest that it is possible to extract energetic and temporal information of the underlying dynamical occupations of the intermediate states from the 2PPE spectra.

Resonance fluorescence of semiconductor quantum dots: Signatures of the electron-phonon interaction - Ahn, K. J.; Förstner, Jens; Knorr, A. (Physical Review B)
Using a fully quantized description of strongly confined electrons interacting with acoustic phonons and the photon field, the nonstationary resonance-fluorescence spectra of a semiconductor quantum dot are investigated. For excitation pulses with durations approaching typical electron-phonon scattering times, the virtual quantum processes yield an observable electron-phonon sideband broadening.
Keywords: tet_topic_qd

Polariton propagation in shallow-confinement heterostructures: Microscopic theory and experiment showing the breakdown of the dead-layer concept - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Rückmann, H. I.; Gutowski, J.; Gust, A.; Alexe, G.; Hommel, D. (Physical Review B)

Coherent propagation of polaritons in semiconductor heterostructures: Nonlinear pulse transmission in theory and experiment - Schumacher, Stefan; Czycholl, G.; Jahnke, F.; Kudyk, I.; Wischmeier, L.; Rückmann, I.; Voss, T.; Gutowski, J.; Gust, A.; Hommel, D. (Physical Review B)

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Excitonic wave packet dynamics in semiconductor photonic-crystal structures - Pasenow, B.; Reichelt, Matthias; Stroucken, T.; Meier, Torsten; Koch, S. W. (Physical Review B)
Significant aspects of the light–matter interaction can be strongly modified in suitably designed systems consisting of semiconductor nanostructures and dielectric photonic crystals. To analyze such effects, a microscopic theory is presented, which is capable of describing the optoelectronic properties of such hybrid systems via a self-consistent solution of the dynamics of the optical field and the photoexcitations of the material. The theory is applied to investigate the local excitonic resonances, which arise as a consequence of the modified Coulomb interaction in the vicinity of a structured dielectric medium. The excitation of a coherent superposition of the spatially inhomogeneous optical transitions induces an intricate wave packet dynamics. In the presence of dephasing and relaxation processes, the coherent oscillations are damped and the photoexcited carriers relax into spatially inhomogeneous quasi-equilibrium distributions.

Nonlinear optical response of the Si ( 111 ) − ( 2 × 1 ) surface exciton: Influence of biexciton many-body correlations - Oszwałdowski, R.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Rohlfing, Michael (Physical Review B)

Time-resolved photoluminescence of type-I and type-II (GaIn) As/Ga (NAs) heterostructures - Hantke, K.; Heber, J. D.; Schlichenmaier, C.; Thränhardt, A.; Meier, Torsten; Kunert, B.; Volz, K.; Stolz, W.; Koch, S. W.; Rühle, W. W. (Physical Review B)
A set of (Ga0.77In0.23)As/Ga(NxAs1−x) heterostructures is studied by time-resolved photoluminescence. Four samples with nitrogen concentrations from x=0.48% up to x=2.2% are investigated at different temperatures and with different excitation densities. The experiments suggest that the heterostructure band offset is type I for x=0.48% and type II for x=2.2%. The situation is more complex for x=0.72% and x=1.25%, since these samples are close to the transition from type I to type II. The experimental findings are analyzed using a detailed microscopic theory. Numerical calculations describe the measured data well. In particular, the interpretation of the experimental results concerning the band alignment is confirmed by the theoretical analysis.

Spatially inhomogeneous optical gain in semiconductor photonic-crystal structures - Reichelt, Matthias; Pasenow, B.; Meier, Torsten; Stroucken, T.; Koch, S. W. (Physical Review B)
The optical and electronic properties of semiconductor heterostructures in the vicinity of photonic crystals are discussed. The theoretical approach provides a self-consistent solution of the dynamics of the electromagnetic field and the material excitations. Due to the influence of the structured dielectric environment on the Coulomb interaction, the exciton resonances and the quasiequilibrium carrier densities in the spatially homogeneous semiconductor become space dependent. It is demonstrated that these inhomogeneities lead to distinct modifications of the optical absorption and gain spectra. As an application, numerically calculated density-dependent optical spectra are analyzed for an array of semiconductor quantum wires which are close to a two-dimensional photonic crystal. The spatial inhomogeneities result in novel excitonic absorption features and modification of the optical gain in these structures.

Optical properties of planar metallic photonic crystal structures: Experiment and theory - Christ, A.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S. G.; Gippius, N. A.; Giessen, H. (Physical Review B)

Control of fine-structure splitting and biexciton binding inInxGa1−xAsquantum dots by annealing - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Radiatively limited dephasing in InAs quantum dots - Langbein, W.; Borri, P.; Woggon, U.; Stavarache, V.; Reuter, Dirk; Wieck, A. (Physical Review B)

Two relaxation mechanisms observed in transport between spin-split edge states at high imbalance - Deviatov, E. V.; Würtz, A.; Lorke, A.; Yu. Melnikov, M.; Dolgopolov, V. T.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Adiabatically driven electron dynamics in a resonant photonic band gap: Optical switching of a Bragg periodic semiconductor - Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Prineas, John P.; Nielsen, Nils C.; Kuhl, Jürgen; Khitrova, Galina; Gibbs, Hyatt M.; Giessen, Harald; Koch, Stephan W. (Physical Review B)
The adiabatic driving of the resonant electron dynamics in a one-dimensional resonant photonic band gap is proposed as an optical mechanism for nonlinear ultrafast switching. Pulsed excitation inside the photonic gap results in an ultrafast suppression and recovery of the gap. This behavior results from the adiabatic carrier dynamics due to rapid radiative damping inside the band gap.
Keywords: tet_topic_qw

Linear and nonlinear pulse propagation in a multiple-quantum-well photonic crystal - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Khitrova, G.; Gibbs, H. M.; Giessen, H. (Physical Review B)
We investigate the temporal and spectral properties of subpicosecond pulses transmitted on the heavy-hole exciton transition through a multiple-quantum-well Bragg structure, exhibiting a one-dimensional photonic band gap. At low light intensities, a temporal propagation beating is observed. This beating is strongly dependent on the optical dephasing time T2 which is dominated by the radiative interwell coupling. In an intermediate intensity regime, the Pauli-blocking nonlinearity leads to gradual suppression of the photonic band gap and vanishing of the linear propagation beating. For highly nonlinear excitation, we find signatures of selfinduced transmission due to Rabi flopping and adiabatic following of the carrier density. Numerical simulations using the semiconductor Maxwell-Bloch equations are in excellent agreement with the experimental data up to intensities for which higher many-particle correlations become more important and self-phase modulation occurs in the sample substrate.
Keywords: tet_topic_qw

Optical dephasing of coherent intersubband transitions in a quasi-two-dimensional electron gas - Waldmüller, I.; Förstner, Jens; Lee, S.-C.; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R. A.; Elsaesser, T.; Hey, R.; Ploog, K. H. (Physical Review B)